USING SINGLE LAYER NEURAL NETWORKS TO PREDICT STOCK PRICES - Haider Abbas abdullah Aljanabi (Scholars Digest Publishing, 2025)
The research aims to shed light on the use of advanced technology in the field of financial investment. By using single-layer neural networks to predict future stock prices. The use of this advanced model over other similar models is to determine the accuracy of this technology in order for investors to resort to using it to achieve unusual returns by investing in stocks that achieve these returns. The results of the research showed that neural networks are highly accurate compared to traditional models, and thus using this technology helps investors make investment decisions quickly and accurately. The research recommended the need to educate investors to resort to technically advanced models in order to help achieve their investment goals and returns that help and encourage increasing the pace of trading within the stock market.
Keywords: Neural networks - single layer - stock prices.